Repeated exposure to odors induces affective habituation of perception and sniffing - Ferdenzi, Camille; Poncelet, Johan; Rouby, Catherine; Bensafi, Moustafa (Frontiers in Behavioral Neuroscience, 2014)
Olfactory perception, and especially hedonic evaluation of odors, is highly flexible, but some mechanisms involved in this flexibility remain to be elucidated. In the present study we aimed at better understanding how repeated exposure to odors can affect their pleasantness. We tested the hypothesis of an affective habituation to the stimuli, namely a decrease of emotional intensity over repetitions. More specifically, we tested whether this effect is subject to inter-individual variability and whether it can also be observed at the olfactomotor level. Twenty-six participants took part in the experiment during which they had to smell two odorants, anise and chocolate, presented 20 times each. On each trial, sniff duration and volume were recorded and paired with ratings of odor pleasantness and intensity. For each smell, we distinguished between “likers” and “dislikers,” namely individuals giving positive and negative initial hedonic evaluations. Results showed a significant decrease in pleasantness with time when the odor was initially pleasant (“likers”), while unpleasantness remained stable or slightly decreased when the odor was initially unpleasant (“dislikers”). This deviation toward neutrality was interpreted as affective habituation. This effect was all the more robust as it was observed for both odors and corroborated by sniffing, an objective measurement of odor pleasantness. Affective habituation to odors can be interpreted as an adaptive response to stimuli that prove over time to be devoid of positive or negative outcome on the organism. This study contributes to a better understanding of how olfactory preferences are shaped through exposure, depending on the individual's own initial perception of the odor.